Efficacy of glyburide vs. metformin in preventing neonatal birth obesity in pregnancies complicated by gestational diabetes mellitus: a systematic review and meta-analysis - Jiang, Wan; Zhang, Hongli; Liu, Xin; Xie, Jianglan; Liu, Jian (Frontiers in Pediatrics, 2025)
BackgroundGestational diabetes mellitus (GDM) has significant implications for both maternal and fetal health, increasing the risk of macrosomia, neonatal hypoglycemia, and long-term metabolic complications in offspring. Given these concerns, a comprehensive evaluation of treatment options, including glyburide and metformin, compared to insulin, is essential to guide clinical practice.MethodsA systematic literature search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, utilizing PubMed, EMBASE, and Web of Science without restrictions on date or language. The focus was on studies comparing oral medications (glyburide or metformin) with insulin for GDM, assessing outcomes, e.g., birth weight and the risk of macrosomia. Studies with non-relevant study designs were excluded. Data extraction and management were conducted with bias assessment using SYRCLE's tool. Statistical analyses were performed using R, incorporating both fixed and random effects models, subgroup analyses, and tests for publication bias.ResultsThis meta-analysis reviewed 23 studies (20 randomized controlled trials and 3 retrospective cohort studies) that evaluated treatments for GDM. The overall risk of macrosomia did not differ statistically between oral medications and insulin [odds ratio (OR) = 0.8534, 95% confidence interval (CI) (0.6271; 1.1614), p = 0.3134]. However, subgroup analysis revealed that glyburide increased the risk (OR=1.3806, p < 0.05), whereas metformin reduced it (OR = 0.6728, p < 0.0001). No statistical difference was found in infant birth weights between oral medications and insulin [mean difference (MD) = 14.3838, 95% CI (−40.7746; 69.5421), p = 0.6093], but subgroup analysis indicating that glyburide increased birth weight [MD = −83.32, 95% CI (−160.74 to −5.91)], and metformin decreased it [MD = 72.80, 95% CI (26.24–119.36)].ConclusionThis meta-analysis suggests that oral medications for GDM do not statistically alter the overall risk of macrosomia or infant birth weight compared with insulin administration. However, glyburide is associated with an increased risk of macrosomia, whereas metformin appears to reduce this risk. Consistent with these findings, glyburide was associated with an increase in infant birth weight, while metformin was associated with a decrease. These findings emphasize the importance of personalized treatment strategies for GDM management.